THE RELATIONSHIP BETWEEN LEISURE AND QUALITY OF LIFE AMONG WORKING WOMEN: A SYSTEMATIC ANALYSIS OF WEB OF SCIENCE LITERATURE 2020–2024 (Isagoge - Journal of Humanities and Social Sciences, 2025)
Today, women play active roles in professional and social life, contributing significantly to the development of societies. However, working women must cope with various factors such as heavy workloads, household and family responsibilities, social life, and health issues. In this process, participation in leisure activities adds meaning and balance to their lives and plays an important role in improving their quality of life. In this study, 61 articles published between 2020 and 2024 in the Web of Science (WOS) database that included the concepts of working women, leisure or quality of life were examined through the document analysis method. Accordingly, the aim of the research is to review studies published in the WOS database in the last five years within the context of working women, leisure and quality of life. The findings indicate an increase in publications on this topic in recent years; most studies were conducted in India and within the field of Public Health, and the International Journal of Environmental Research and Public Health was identified as the journal with the highest number of publications. Most of the studies were indexed in SCIE journals and published in journals with a moderate impact factor. The majority of the studies were quantitative in nature and mainly used questionnaires as data collection tools. As a result, it was determined that working women have difficulties in planning their leisure due to job and household responsibilities, which negatively affects their quality of life, whereas participation in leisure activities has positive effects on health, stress management, and overall life quality. In this regard, it is recommended to strengthen spousal support and develop positive employer policies to enhance leisure participation and improve the quality of life among working women.